Effect of Mandibular Advancement Device Therapy on the Signs and Symptoms of Temporomandibular Disorders - Ritva Näpänkangas; Antti Raunio; Kirsi Sipilä; Aune Raustia (eJournal of Oral Maxillofacial Research)
Objectives: Mandibular advancement device therapy is effectively used in the treatment of obstructive sleep apnea, but also several side effects in the masticatory system have been reported. The aim of this study was to evaluate the subjective symptoms and clinical signs of temporomandibular disorders connected to mandibular advancement device therapy. Material and Methods: The material consisted of 15 patients (9 men and 6 women, mean age 51.1 years, range 21 to 70 years) diagnosed with obstructive sleep apnea (OSA). Subjective symptoms and clinical temporomandibular disorders (TMD) signs were recorded at the beginning of the treatment (baseline) and at 1-month, 3-month, 6-month and 24-month follow-ups. The degree of TMD was assessed using the anamnestic (Ai) and the clinical dysfunction index (Di) of Helkimo. For assessing the effect of TMD the patients were divided in discontinuing and continuing groups. Results: According to Ai and Di, the severity of TMD remained unchanged during the follow-up in most of the patients. Temporomandibular joint (TMJ) crepitation was found more frequently in discontinuing patients at all follow-ups. The difference was statistically significant (P < 0.05) at the six-month follow-up. Masticatory muscle pain during palpation was a frequent clinical sign at the baseline and during the follow-up period but the difference between discontinuing and continuing patients was not significant. Conclusions: It seems that signs and symptoms of temporomandibular disorders do not necessarily increase during long-term mandibular advancement device therapy. However, it seems that patients with clinically assessed temporomandibular joint crepitation may discontinue their mandibular advancement device therapy due to temporomandibular disorders.